#TITLE_ALTERNATIVE# - AULYA D (NIM: 15414058), MAHENDRA
Land was the most important aspect on doing development because development taking place on the land. Therefore, the availability of some prime and mature land are some of the determinant factors of successful development. Prime and mature land are usually measured through the nominal value of the selling price of the land. The level of nominal prices are influenced by many factors. One of those determinants of land prices is the existence and accessibility of infrastructure, because the existence and accessibility can affect the maturity of the land. One of the infrastructure provision that has a large influence on land prices is MRT transportation infrastructure, because MRT comes with a variety of potential benefit. The existence of MRT which is supported by the implementation of the TOD concept will provide enormous positive benefits, which of course will be captured by land in the form of price increases. The Dukuh Atas area which has been designated as a regional scale TOD center will certainly experience an increase in the price of the land. In addition to the Dukuh Atas TOD Zone, the TOD Harmoni area which has similar land uses and similarities in intermodal transportation support also certainly experiences an increase in land prices. Therefore, this study will explain the land price dynamics model that occurs in the TOD Dukuh Atas area and TOD Harmoni area, and find out how much influence some of the land price factors on the dynamics that occur. This research uses hedonic regression analysis method and descriptive analysis which aims to explain the land price dynamics model that occurs, using the Land Value Zone (ZNT) data from the Ministry of ATR / BPN as data for the land price variable, so that the unit of variable analysis in this study is carried out at the level of land zone details. In this study, it is known that the price of land for the two delineation areas has accumulatively increased from 2015 to 2018. The increase or change in land prices is influenced by the distance of the land zone to the Harmoni Busway Stop, Crime Rate, Land Prices of 2017, Health Facilities, Facilities of Education, Public Space, and Toll Exit. In addition there is also a tendency for the influence of the existence of roads, especially arterial roads, as well as the influence of the Zoning Regulations and RDTRP that apply in forming nominal land prices. Keywords: land price, land value zone (ZNT), transit oriented development, dukuh atas, harmoni, hedonic pricing method